Health‐related quality of life maintained over time in patients with relapsed or refractory multiple myeloma treated with daratumumab in combination with bortezomib and dexamethasone: results from the phase III CASTOR trial. (8th February 2021) - Hungria, Vania; Beksac, Meral; Weisel, Katja C.; Nooka, Ajay K.; Masszi, Tamas; Spicka, Ivan; Munder, Markus; Mateos, María‐Victoria; Mark, Tomer M.; Qi, Ming; Qin, Xiang; Fastenau, John; et al.
Summary: In the phase III CASTOR trial, daratumumab, bortezomib and dexamethasone (D‐Vd) significantly extended progression‐free survival compared with bortezomib and dexamethasone (Vd) alone in patients with relapsed/refractory multiple myeloma (RRMM). Here, we present patient‐reported outcomes (PROs) from the CASTOR trial. PROs were assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30‐item (EORTC QLQ‐C30) and the EuroQol 5‐dimensional descriptive system questionnaire. Treatment effects through Cycle 8 were measured by a repeated measures mixed‐effects model. After Cycle 8, PROs were only collected for patients in the D‐Vd group who continued on daratumumab monotherapy. Compliance rates for PRO assessments were high and similar between treatment groups. Mean changes from baseline were generally similar between treatment groups for EORTC QLQ‐C30 global health status (GHS), functioning and symptoms, and did not exceed 10 points for either treatment group. Subgroup analyses were consistent with the results observed in the overall population. There was no change in patients' health‐related quality of life for the first eight cycles of therapy; thereafter, patients treated with daratumumab over the long‐term reported improvements in GHS and pain. These results complement the significant clinical benefits observed with D‐Vd in patients with RRMM and support its use in this patient population.